Rx and its downstream factor, Musashi1, is required for establishment of the apical organ in sea urchin larvae - Yaguchi, Junko; Yaguchi, Shunsuke (Frontiers in Cell and Developmental Biology, 2023)
Acetylcholine, a vital neurotransmitter, plays a multifarious role in the brain and peripheral nervous system of various organisms. Previous research has demonstrated the proximity of cholinergic neurons to serotonergic neurons in the apical organ of sea urchin embryos. While several transcription factors have been identified as playing a role in the development of serotonergic neurons in this region of a sea urchin, Hemicentrotus pulcherrimus, comparatively little is known about the specific transcription factors and their spatiotemporal expression patterns that regulate the development of cholinergic neurons. In this study, we establish the requirement of the transcription factor Rx for the development of cholinergic neurons in the apical organ of the species. Furthermore, we investigate the role of the RNA-binding protein Musashi1, known to be involved in neurogenesis, including cholinergic neurons in other organisms, and demonstrate that it is a downstream factor of Rx, and that choline acetyltransferase expression is suppressed in Musashi1 down-regulated embryos. Our research also highlights the intricate network formed by neurons and other cells in and around the apical organ of sea urchin larvae through axons and dendrites, providing possibility for a systematic and complexed neural pattern like those of the brain in other organisms.